2013
DOI: 10.1021/nn3046709
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Active Site in Nitrogen-Doped Graphene for the VO2+/VO2+Redox Reaction

Abstract: Nitrogen-doped graphene sheets (NGS), synthesized by annealing graphite oxide (GO) with urea at 700-1050 °C, were studied as positive electrodes in a vanadium redox flow battery. The NGS, in particular annealed at 900 °C, exhibited excellent catalytic performance in terms of electron transfer (ET) resistance (4.74 ± 0.51 and 7.27 ± 0.42 Ω for the anodic process and cathodic process, respectively) and reversibility (ΔE = 100 mV, Ipa/Ipc = 1.38 at a scan rate of 50 mV s(-1)). Detailed research confirms that not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
191
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(204 citation statements)
references
References 58 publications
13
191
0
Order By: Relevance
“…Then, upon cooling, the solid graphene is readily collected. Jin et al [131], prepared nitrogen-doped graphene sheets (NGS) by annealing graphite oxide with urea under an Ar atmosphere for 3 h in a tubular furnace at 700-11,050°C. The NGS is studied as positive electrode in vanadium redox flow battery.…”
Section: Graphite Conversionmentioning
confidence: 99%
“…Then, upon cooling, the solid graphene is readily collected. Jin et al [131], prepared nitrogen-doped graphene sheets (NGS) by annealing graphite oxide with urea under an Ar atmosphere for 3 h in a tubular furnace at 700-11,050°C. The NGS is studied as positive electrode in vanadium redox flow battery.…”
Section: Graphite Conversionmentioning
confidence: 99%
“…Therefore, apart from the amount of oxygen functional groups (C=O, C-OH) on the surface, other features related to the electrode activity, such as wettability and adsorption of vanadium onto surface electrode become also decisive. It is worth mentioning that the formation of Carbon-Nitrogen-Vanadium intermediate especially via quaternary and/or oxidic nitrogen groups [4] is a key step for the enhancement of the electrocatalytic activity [2,3], facilitating the electron transfer in the electrode/electrolyte interface M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…The improvement was attributed to improved surface wetting as a result of surface nitrogen functional groups, reduced activation energy resulting from bulk (quaternary) nitrogen doping for V-O bond formation, and improved electronic conductivity also associated with nitrogen doping of the bulk carbon. Jin et al [19] further confirmed the importance of quaternary nitrogen, demonstrating that it was the most likely active reaction site because other surface localized nitrogen species (pyridinic-N and pyrrolic-N) would become inactive through protonation of their lone electron pairs.…”
Section: Introductionmentioning
confidence: 95%
“…Carbon fiber based materials (CFBM) such as carbon felts (CFs) [14][15][16][17], and papers [18] meet many of these requirements, along with being robust, relatively inexpensive, and easily manufactured, and thus they have gained considerable research and commercial attention. However, these prospective carbon materials suffer from relatively poor electrochemical activities leading to poor reaction kinetics and reversibility, particularly for positive electrodes [19]. Many efforts have been undertaken to remedy these aforementioned shortcomings, with several strategies being pursued to enhance and modify the surface area and surface chemistry.…”
Section: Introductionmentioning
confidence: 99%